Verbal communication of the conductor with the chorus as the main tool of their interaction in the process of conducting activities - Варганич, Г. О. (Scientific notes of the pedagogical department, 2018)
In this article the importance and role of verbal communication of the conductor with the choir are analyzed. The structural components of verbal communication of conductor with chorus are determined.The solution to this problem allows us to consider the «language of the conductor» in more detailed way, and with the help of this «language» the conductor's activity is carried out. The author notes that the subject of the communication of the conductor is the choir collective, and communication between them will not occur, unless the sign system – the score of the musical composition is included.The author believes that verbal communication takes place in the form of a dialogue, where two partners – the choir and the conductor – are holding a conversation by means of singing at the musical level.Conducting, as a kind of communication between the conductor and the performer, is considered in contemporary musicology as the art of managing the collective performance of a musical work (orchestra, choir). The art of conducting is a specially designed system of gestures, facial expressions.The sign system of conducting in the textbooks began to be named conductor's technique. The technique of conducting is the language on which the conductor turns to the chorus or orchestra. The conductor must own it, the orchestra and the choir must understand it.The author of the article distinguishes a number of functions that must be performed by the conductor. Among them are: organizational functions, functions of the educator, functions of the artist, functions of the interpreter.In order to cover our problem of communication between conductor and performers, there two functions are important for us:- creation of intra-auditory imagination about a musical composition;- translation of your musical imagination into a sign action, sign system.Conductor takes possession of a sign system of musical text to overcome the intra-auditory imagination of the sound of a musical work.In the article, the author emphasizes that the lack of a score musical composition deprives the conductor of the possibility to conduct. At the same time, the lack of musical material for the performers does not give an opportunity to communicate with the conductor.The signs of conducting are the language of the conductor, that helps him «to speak» with the performers, and therefore the knowledge of the language by the performers is obligatory, and in the process of working with the collective the conductor teaches to it, which makes it possible to perform the function of the interpreter of musical works.The author emphasizes that the conductor in the rehearsal process constantly uses verbal communication with the choir as the most accessible form of explanation of rumorous musical notions about the score, about the sign system of conducting. All processes of work with a choir need to be explained by word.The forms of the verbal communication are analyzed, namely: explanation, narration, illustration, demonstration, remarks, commands and requests. All forms are considered by the author of the article in two ways, and not just from the conductor`s point of view.At the end of the article the author makes a conclusion that the verbal communication of the conductor with the choir is regarded as one of the most important methods of conducting activity that requires special training.